ANALYSIS OF BUDGET DISTRIBUTION IMBALANCE BETWEEN QUARTERS AT HIGH SCHOOL GOTONG ROYONG KOTA BANGUN: IMPACT ON FINANCIAL MANAGEMENT - Saparuddin, Muhammad; Haryaka, Usfandi Haryaka (BEduManagers Journal : Borneo Educational Management and Research Journal, 2024)
Effective budget management is essential for the smooth operation and development of an educational institution. This study aims to analyze the imbalance of budget distribution between quarters at SMA Gotong Royong Kota Bangun in fiscal year 2024, and evaluate its impact on financial management and school operations. Using a qualitative descriptive approach, data were collected through budget documents and interviews with financial managers and school principals. The results showed that there was a striking imbalance in budget distribution between quarters. The budget, which totaled IDR 72,128,000, was dominated by personnel expenditure (81.52%), with limited allocations for capital expenditure (4.62%) and facility maintenance (9.24%). Quarter III saw an unplanned surge in the budget, while Quarter II saw a significant decrease, especially in the allocation for capital expenditure and maintenance. Factors causing this imbalance include inadequate budget planning, limited funds at the beginning of the year, and sudden changes in needs. As a result, schools experienced operational disruptions, such as limited infrastructure development and minimal investment in technology. This budget imbalance also reduces the efficiency of school financial management. Based on these findings, it is recommended that SMA Gotong Royong Kota Bangun conduct more thorough and equitable budget planning between quarters, taking into account long-term needs and facility development. Increased allocations for capital expenditure and facility maintenance also need to be considered so that financial management is more efficient and supports the quality of education in a sustainable manner.